PECULIARITIES OF CALLUSOGENESIS AND MORPHOGENESIS OF PRIMARY EXPLANTS IN VITRO OF DIFFERENT RAPE GENOTYPES (BRASSICA NAPUS L.) - Klyachenko, O. L.; Shofolova, N. V.; Chernii, S. O. (Scientific Progress & Innovations, 2020)
Currently there is important the creation of new genotypes of rape, combining high productivity, technological qualities, as well as resistance to various environmental stressors, based on the use of the new practical developments to improve breeding materials of this crop. One of the effective biotechnological methods which allows to expedite the reproduction of valuable breeding material and obtain a new one is the use of morphogenesis of callus biomass. The study was conducted in the training laboratory of plant biotechnology of the Department of Ecobiotechnology and Biodiversity of National University of Life and Environmental Sciences of Ukraine. There were studied 9 varieties and hybrids of winter and spring rapeseed: Danhal, Chornyi veleten, Nelson, Aliot, NK Petrol, NK Тechnic, Cliff, Geros. Callus tissue was planted on 3 variants of Murasige-Skoog medium with different growth regulators 6-BAP, IOC, NOC, 2,4-D. As a result of study it was found that the formation of callus on the K1 medium was observed on the 7th day of cultivation, on the 12th day 72–100% of the explosives formed the calluses. On the second nutrient medium K2 compared to medium K1 a slight decrease in the growth index of rapeseed was found. The formation of callus tissue was observed, which differed in morphological features and a slight increase in biomass, the minimum weight was 122,0 mg and the maximum – 187,9 mg. On K3 medium, a low callus growth index with the lowest mass was observed, with the exception of the Nelson winter rapeseed variety, in which the index increased 1.7 times. The formation of callus tissue of dense consistency of varieties and hybrids of winter and spring rapeseed was observed for 21 days on medias K1 and K2. The medium with the addition of 6-BAP, where later leaf and stem structures were found from the morphogenetic callus, was used for the regeneration of explants of different rapeseed genotypes. Thus, according to the results of the study, it was found that the optimal medium for the growth of morpho- and callusogenesis is the medium containing 6-BAP, on which the formation of a dense callus was observed in almost all rapeseed genotypes.